PENGARUH KECEPATAN POTONG, GERAK MAKAN DAN KETEBALAN PEMOTONGAN TERHADAP GETARAN BENDA KERJA PADA PROSES SEKRAP - Mulyadi, Santoso (ROTOR, 2012)
Shaping  machine  is  a  machine  tool  used  to  modify  the  surface  of  the workpiece into a flat surface, good story, angled, and the flow corresponding to the shape  and  size  desired.  Shaping  process  is  a  process  similar  to  the  lathe,  the difference is in motion the process of intersection. In the process shaping machine tools with straight main motion back and forth vertically or horizontally. Chisel cut motion  in  a  straight  motion  of  the  workpiece  is  translational.  In  this  case  the workpiece and cutting tool is at rest moving straight translation. At the chisel to move back, move the workpiece also bait (feeding). So your back will chisel stuck in a moving workpiece. Shaping machinery industry in the world used to work on areas of flat, convex, concave, disorderly, in a horizontal position, vertical, or oblique, etc. From the research results can be seen the effect of the parameters used to the chatter values obtained chisel and roundness. Can be seen carving the smallest value of the vibration generated from experimental data 1 is =0.5562 m/s2 at n = 5 m/min, f = 0,2 and a = 1 mm. While the biggest chisel vibration acceleration values obtained from experimental data collection to 27 for = 5,1659 m/s2 at n = 11 m/min, f = 0,6 and a = 2 mm. The results in general that the value of vibration acceleration, after the feeding motion raised the value of vibration acceleration of the workpiece increases, this is because the larger the feed motion is used then the resulting anger is also growing thicker so that the necessary cutting force increases. As a result, the tangential force is also up and cause the radial force and moment coupling. Keywords: cutting speed. feeding, dept of cut,  workpiece and vibration.